Mutation analysis at the lipoprotein lipase gene locus in two South African kindreds - Hassan, Mohammed Fahri (Division of Chemical Pathology, 2018)
Familial lipoprotein lipase (LPL) deficiency is a rare disorder of lipid metabolism associated with massive chylomicronaemia. Patients often present early in life with abdominal pain, pancreatitis, hepatosplenomegaly, eruptive xanthomata and zero to near zero levels of LPL activity in post-heparin plasma. The genetic heterogeneity underlying this disease is well-characterised and over 40 mutations have been described at the LPL gene loci. In this report three mutations are described at the LPL locus in two unrelated probands, namely, JJ (Kindred I) and LB (Kindred II). JJ presented early in childhood with signs and symptoms suggestive of LPL-deficiency. These were abdominal pain, hepatosplenomegaly and a markedly reduced LPL activity (38% of normal) in post-heparin plasma. DNA studies showed JJ to be a compound heterozygote for two point mutations in the LPL gene, these being, the I194T and C418Y substitutions, which occur in exons 5 and 9, respectively. Several mutation detection systems were set up as part of the characterisation and screening workup for these mutations; these were, allele-specific oligo nucleotide (ASO) hybridisation, "ARMS" PCR, PCR-SSCP, RT-PCR and DNA sequence analysis. In an earlier separate study, in vitro transfection results showed that the I194T mutant was catalytically inactive. Our findings of zero LPL activity in JJ's post-heparin plasma, implies that the C418Y mutation is also likely to produce an inactive protein product. The differences in LPL activity observed during the pre- and post-pubertal stages, if not artefactual, may be due to differential processing of LPL during human development with loss of activity post puberty. LB was first diagnosed with pancreatitis during the third trimester of her pregnancy. Although her child, BB, was successfully delivered by caesarean section, LB died of haemorrhagic pancreatitis with the marked hyperlipidaemia being suggestive of an underlying deficiency in LPL activity. Genomic DNA from her parents was first subjected to mutation analysis, since only slide specimens of post-mortem material were available from LB. Maternal DNA revealed a 0-A transition at nucleotide position 1516 which results in the substitution of lysine for glutamic acid at codon 421 in exon 9 (E421K), while paternal DNA show a single polymorphism at codon 108 in exon 3 of the LPL gene. Analysis of archival DNA obtained from histopathological slides of spleen tissue from LB also showed the E421K mutation. This mutation was also detected in her offspring, BB indicating maternal inheritance in three generations. While, this mutation may produce a catalytically defective product, the evidence is insufficient to propose a role for LPL deficiency as the primary cause of death in this patient, hence the search for a second mutation in the LPL gene of LB is imperative to establish this association.